PREPARATION, CHARACTERIZATION AND ORANGE II REMOVAL UNDER VISIBLE LIGHT RADIATION OF Cu-Ni/Ti02 PHOTOCATALYST - RIAZ, NADIA (2012)
Photocatalytic degradation of a model azo dye, Orange II, was investigated over bimetallic Cu-Ni/Ti02 photocatalysts. In the present study the introduction of Cu and Ni onto Ti02 surface was with the intention to reduce the band gap of the photocatalyst for enhanced visible light absorption via three methods: co precipitation (CP), deposition-precipitation (DP) and wet impregnation (WI) methods with different Cu:Ni mass composition (10:0, 9:1,7:3,5:5,3:7, I :9 and 0:10). The physical and chemical properties of the modified Cu-Ni doped photocatalysts were investigated using Thermogravimetric Analysis (TGA), Fourier-Transformed Infrared Spectroscopy (FTIR), Point of Zero Charge (PZC) determination, powder X-ray Diffraction (XRD), BET surface area analysis, Field-emission Scanning Electron Microscopy-Energy Dispersive X-Ray Spectroscopy (FESEM-EDX), High Resolution Transmission Electron Microscopy (HRTEM), Diffuse Reflectance UVVis Spectroscopy (DRUV-Vis) and Temperature-programmed Reduction (TPR). The raw photocatalysts were activated by calcination at three different temperatures (180°C, 200°C and 300°C) for I h duration. The PZC of Cu-Ni/Ti02 photocatalyst shifts to a more basic value compared to the bare Ti02 (3.8). Photocatalyst particles were spherical with slight agglomeration and high metal dispersion was achieved confirmed by XRD and FESEM-EDX analyses. The presence of Cu-Ni mixed oxide was detected by TPR analysis. The surface area of Cu-Ni/TiOz photocatalysts was higher compared to that of bare TiOz. Incorporation of Cu, Ni, and Cu-Ni onto Ti02 resulted in the shift of absorption spectra into visible region with reduced bandgap energy (2.74 eV) as confirmed by DRUV-Vis spectroscopy. The synthesized CuNi/Ti02 photocatalysts were screened for Orange II decoloration efficiency against different reaction parameters. The parameters studied were the effect of different photocatalysts preparation methods, calcination temperature, Cu:Ni mass composition, initial pH, metal loading, photocatalyst loading, initial dye concentration and oxygen bubbling.